GAYA BAHASA DALAM NOVEL TAMU TAK DIUNDANG KARYA ERBY S. DAN SINDY LASIFA - Alan Alan; Haedariah Haedariah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem in this study is what language styles are used in the novel Tamu Tak Diundang by Erby S. and Sindy Lasifa. The aim is to describe what language styles are used in the novel. This study can provide benefits for the development of scientific insight into Indonesian literature, especially in the study of pure linguistics.This type of research is a Qualitative Descriptive research, the method used is a qualitative method. The source of this research is the novel Tamu Tak Diundang by Erby S and Sindy Lasifa. The data collection technique used is the document review technique. The data of this study were analyzed using a Sociolinguistic approach. It is concluded that the Language Style contained in the novel Tamu Tak Diundang by Erby S and Sindy Lasifa. which consists of fifteen quotes found by researchers which are divided into several parts, namely, Hyperbole, Association, Metaphor, Personification, Repetition, Allegory, Cynicism, Totem Pro Parte. So that in the quotations that can be discussed in the results of this study only Fifteen Quotations. The researcher expects the next researcher to be able to research or study other things contained in the novel Tamu Tak Diundang by Erby S and Sindy Lasifa, which are even broader.